ASSESSMENT OF LOCOMOTIVE FLEET OPERATION USING THE METHODS OF DECREASING DIMENSIONS - Bodnar, B. Y.; Ochkasov, A. B.; Grusheckyna, T. S.; Bodnar, Y. B. (Science and Transport Progress, 2019)
Purpose. The main purpose of the work is to reduce the time for analysis and increase the efficiency of processing statistical information on assessing the locomotive fleet operation through the use of methods to reduce the data dimensionality. Methodology. To conduct the study, the methodology for constructing an arbitrary process index was chosen. Using the methodology allows selecting from the total set of parameters those components that are the most informative. Using the method of hierarchies analysis based on the obtained main components, it is possible to construct a single generalizing indicator. Findings. The approaches to improving the existing system of indicators for accounting the operation of locomotives were analyzed. The expediency of using dimensionality reduction methods to analyze the locomotive operation was substantiated. Using the method of main components, the most informative indicators of locomotive operation and the degree of their influence on the general level of traffic safety in locomotive economy, the implementation of the maintenance system are determined. The examples of the analysis of locomotive economy indicators using the proposed methodology, index of performance of maintenance system, traffic safety indices and operational safety in locomotive economy are given. The locomotive economy was analyzed through a joint review of the proposed integrated indices, as well as quantitative and qualitative indicators of the locomotive use. The difference between these indicators shows a deterioration or improvement in the traffic safety state, taking into account the volume of work performed. Increase in the operational traffic safety coefficient over the safety index shows a deterioration in the traffic safety state, despite a decrease in the absolute values of indicators characterizing the level of traffic safety in locomotive economy. Originality. For the first time, it was proposed to evaluate the traffic safety state in locomotive economy through the difference between the traffic safety and operational safety indices. Practical value. To analyze the operation of locomotive fleet, it is advisable to use the methods to reduce the data dimensionality. To assess the traffic safety state, it is more advisable to use the operational safety index, since it takes into account the volumetric performance indicators of locomotive economy.